Care System Versus Transmitted Light Wavefront Pattern of Contact Lenses. Issue 3 (May 2017) - Chiericati, Stefano; Borghesi, Alessandro; Cozza, Federica; Ferraro, Lorenzo; Acciarri, Maurizio; Farris, Stefano; Tavazzi, Silvia
Abstract : Objectives: This article compares the optical performance of soft contact lenses (CLs) treated with multipurpose or hydrogen peroxide care systems. Methods: The investigated care systems were (1) 3% hydrogen peroxide solution Oxysept (Abbot Medical Optics, Abbott Park, IL) and (2) multipurpose solution Regard (Vita Research, Ariccia, Italy). Three types of silicone hydrogel CLs were studied (comfilcon A, lotrafilcon B, and balafilcon A), unworn and exposed for 30 times to the solutions, which were replaced every 8 hr. The optical performance of the CLs was evaluated through the on-eye transmitted light wavefront patterns by considering new CLs as references. The surface morphology of the CLs was investigated by scanning electron microscopy. Results: Statistically significant modifications in the range 0.1 to 0.3 μm of Zernicke coefficients and modifications of the root mean square of the wavefront aberration function were found for CLs treated with multipurpose solution, in agreement with the observed modifications of the surface morphology. Statistically significant changes were also found after exposure to the hydrogen peroxide solution, but the variation of the Zernicke coefficients was found lower than 0.1 μm, thus being negligible in CL optical performances. Conclusions: In addition to disinfection ability and ocular surface reactions, CL care systems are different in solution-related CL optical performance. Multipurpose solutions may affect the CL surface morphology with significant modifications of the transmitted light wavefront pattern.